Assessment of Nurses’ Knowledge of the Glasgow Coma Scale in a Saudi Tertiary Care Hospital: A Cross-Sectional Study - Roaa Alsharif; Salsabil Abo Al-Azayem; Nimah Alsomali; Wjoud Alsaeed; Nawal Alshammari; Abdulaziz Alwatban; Yaseen Alrabae; Razan Orfali; Faisal Alqarni; Ahmad Alrasheedi (Clinical and Translational Neuroscience)
The Glasgow Coma Scale (GCS) is essential for assessing traumatic brain injury and predicting patient outcomes, yet studies indicate that nurses often have only a basic understanding of the GCS. In Saudi Arabia, research on this topic is limited, suggesting a need for improvement in nurses’ GCS knowledge. This study aimed to evaluate the knowledge and proficiency of 199 staff nurses at King Fahd Medical City in Riyadh, Saudi Arabia, regarding GCS usage and to identify the factors impacting their competence. A descriptive, cross-sectional survey was conducted, and the data were analyzed using SPSS version 23.0. The results showed that 81.4% of nurses had an average level of GCS knowledge, with a mean score of 8.8 ± 1.826. Only 13.6% demonstrated good knowledge, while 5% had poor knowledge. A significant correlation was found between GCS knowledge and nurses’ departments (χ2(2) = 19.184, p < 0.001). The study concludes that GCS knowledge among nurses in this Saudi Arabian center is moderate, highlighting the need for continuous education programs to enhance their competence in GCS assessment.